Studies in Modern Religions, Religious Movements and the Bābī-Bahā'ī Faiths. - Moshe Sharon (Editor) (Numen Book Series, 2004)
In this book leading scholars contribute comprehensive studies of the religious movements in the late 18th and 19th centuries: the Hassidic movements in Judaism, the Mormon religion, in Christianity, and the Bābī-Bahā'ī faiths in Shī'te Islam. The studies, introduced by the editor's analysis of the underlying common source of this religious activity, lead the reader into a rich world of messianism, millenniarism and eschatological thought fueling the intense modern developments in the three major monotheistic religions.